Rome and the ancient world - Corbishley, Mike. (New York : Facts On File, 1993)
Explores the history of the Roman Empire and the world outside the Empire, including ancient China, ancient India, and the empires of Africa.
The rise of Rome -- The Roman Empire -- Everyday life in the Empire -- Life in ancient China -- Ancient India -- The Kushans -- The Parthian and Sassanian Empires -- The empires of Africa.
Includes bibliographical references (p. 77), index, glossary, and chronology.
Book Report.
Library Talk.
Wilson's Junior High School.
6.5
4-6
Keywords: History, Ancient -- Juvenile literature; History, Ancient; Ancient history; Rome -- History -- Juvenile literature; Rome -- History; Rome -- History